Recuperação de fotografias de agremiações futebolísticas profissionais de Santa Maria - RS através de sistema gerenciador de conteúdo - Tittelmeyer, Alexander Rossatto (2012)
This Master's thesis presents a historical review of proposals for professional football associations of Santa Maria-RS through the Cultural Heritage and the use of images in the composition of a content management system based wiki that refers to the history of the clubs. The intent is to demonstrate the construction of a joint work of the Cultural Heritage itself, as well as topics such as History, Memory, Archives Diffusion and Photography, and Information Technology, with aspects related to the nature of football sports bodies, demonstrating the importance and relevance of the combination of themes separable and apparently has not studied thoroughly, at least as consistent with local realities of the municipality of Santa Maria-RS. The research demonstrates an institutional memory of the rescue of sporting clubs in question, its organization and retrieval, as a way of highlighting the emergence of a field of work related to the sports area. The work is divided into chapters, which deal with the broadcast, Archives Diffusion, History, Cultural Heritage, Memory, Photography and the Use of Images. Complementary parts of the research dealing exclusively with the football and its history, divided into national, regional and municipal levels, demonstrating the relevance and significance of the theme in several aspects, such as the sociological and cultural, among others. To this end, we sought the preparation of an electronic instrument to characterize the history of the club through images and additions in the form of a virtual encyclopedia on finding practical solutions that meet user needs in relation to the world of football.